Test of Bamboo Leaf Bacterial Potential on the Growth and Yield of Shallot Plants (Allium ascalonicum L.) - Sulle, Atrieda; Husain, Indriati; Irhamnawati Pulogu, Siska; Zakaria, Fauzan; Yamin, Mayasari (International journal of technology and education research, 2026)
This research was carried out at the Laboratory of the Department of Agrotechnology, Faculty of Agriculture, Gorontalo State University and at the Green House of the Gorontalo Agricultural Assembly and Modernization Agency from December 2024 to April 2025. This study aims to determine the effect of soaking onion bulbs with bamboo leaf bacterial isolate on the growth and yield of shallot plants and to obtain bamboo leaf bacterial isolate that has the potential to affect the growth and yield of shallot plants. The study was designed using a Random Design Group (RDG) with a suspension treatment of bamboo leaf bacterial isolates consisting of seven types of bacterial isolates that have not yet been identified, namely, X1, X2, X3, X4, X5, X6, X7, and X0 as controls (without bacterial suspension). The parameters measured were plant height, number of leaves, number of seedlings, number of bulbs, weight of wet bulbs, and weight of dry bulbs. The observation data was analyzed using Analysis of Variance (ANOVA α = 5%), and if the results were significantly different, DMRT was further tested at the level of 5%. The results showed that the X2 bacterial isolate suspension treatment had a real effect on the number of seedlings, and had a good influence on the parameters of the number of bulbs and the weight of dry bulbs.